Culture and the Spatial Dissemination of Ideas Evidence from Froebel's Kindergarten Movement - Oliver Falck; Stefan Bauernschuster (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Friedrich Froebel, a German pedagogue, established the first kindergarten worldwide in Thuringia in 1839. We study the spatial dissemination of the kindergarten movement in Germany in the 19th and beginning of the 20th century. Spatial dissemination can be explained by the cultural proximity, measured by dialect similarity at the end of the 19th century, to Froebel's place of activity. We further show that the spatial pattern of child care use is highly persistent over time. End of 19th century cultural proximity to Froebel s place of activity can explain the spatial pattern of child care use in the 1990s and 2000s.
Keywords: N33; J13; Z13; 330